BLISS is a versatile and quantitative method for genome-wide profiling of DNA double-strand breaks - Winston X. Yan (Nature Portfolio, 2017)
Double-strand breaks are a major DNA lesion that can occur by endogenous and exogenous processes. Here the authors present BLISS—Breaks LabellingIn Situand Sequencing—to map breaks across the genome.